Early-Onset Friedreich's Ataxia With Oculomotor Apraxia - Amene Saghazadeh; Sina Hafizi; Firouzeh Hosseini; Mahmoud Reza Ashrafi; Nima Rezaei (Acta Medica Iranica, 2017)
Friedreich’s ataxia (FRDA) is a rare autosomal recessive spinocerebellar ataxia which in the majority of cases is associated with a GAA-trinucleotide repeat expansion in the first intron of Frataxin gene located on chromosome 9. The clinical features include progressive gait and limb ataxia, cerebellar dysarthria, neuropathy, optic atrophy, and loss of vibration and proprioception. Ataxia with ocular motor apraxia type 1 (AOA1) is another autosomal recessive cerebellar ataxia which is associated with oculomotor apraxia, hypoalbuminaemia, and hypercholesterolemia. Here we describe two siblings (13- and 10-year-old) display overlapping clinical features of both early-onset FRDA and AOA1. Almost all of laboratory test (including urinary analysis/culture, biochemistry, peripheral blood smear, C-reactive protein level, erythrocyte sedimentation rate-1h) results were within the normal range for both patients. Due to the normal laboratory test results; we concluded that the diagnosis was more likely to be FRDA than AOA1. Therefore, neurologists should bear in mind that clinical presentations of FRDA may vary widely from the classical phenotype of gait and limb ataxia to atypical manifestations such as oculomotor apraxia.